2018
DOI: 10.19087/imv.2018.7.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Sinergi Bioaktivitas Daun Tapakdara (Chatarantus Roseus) dan Pegagan (Centella Asiatica) terhadap Proses Penyembuhan Luka Insisi pada Anjing Kintamani

Abstract: Obat herbal masih banyak digunakan masyarakat untuk mengobati beberapa penyakit terutama di negara-negara berkembang. Hal ini karena secara budaya mudah diterima dan rendahnya efek samping yang ditimbulkan. Tanaman tapakdara (Cantharantus roseus) dan pegagan (Centella asiatica) merupakan tanaman obat yang terbukti secara empiris dapat digunakan sebagai obat gangguan pada kulit seperti dermatitis, eksim, jerawat, luka. Penelitian ini bertujuan untuk mengevaluasi sinergi bioaktivitas ekstrak daun tapakdara dan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…The peak of angiogenesis was at day 5 (Prasetyo et al, 2010). In the same pattern, angiogenesis declined at day 15 (Ferdinandez et al, 2013). Other studies have shown that angiogenesis starts on day 1 after wound induction, peaks at day 5, and declines from day 7 to day 14 (Setiawan et al, 2015).…”
Section: Variablesupporting
confidence: 65%
“…The peak of angiogenesis was at day 5 (Prasetyo et al, 2010). In the same pattern, angiogenesis declined at day 15 (Ferdinandez et al, 2013). Other studies have shown that angiogenesis starts on day 1 after wound induction, peaks at day 5, and declines from day 7 to day 14 (Setiawan et al, 2015).…”
Section: Variablesupporting
confidence: 65%
“…Secara fisiologis, saat terjadi perlukaan pada kulit, maka akan terjadi secara otomatis proses penyembuhan dan regenerasi sel sebagai respon fisiologis tubuh yang melalui fase inflamasi, fase poliferasi dan fase remodeling [6] . Proses penyembuhan luka adalah suatu proses fisiologi yang melibatkan komponen -komponen berupa sel-sel dan substansi kimia yang di mana ini diperlukan di dalam proses inflamasi, angiogenesis, dan deposisi kolagen.…”
Section: Pendahuluanunclassified
“…In addition, empirically tapak dara is also known to have properties as analgesic (anti-pain) and anti-inflammatory (anti-inflammatory). This is also based on the many studies on the utilization of tapak dara leaf extract as anti-inflammatory (Putri et al, 2019) wound healing and antipyretic drugs whose effectiveness has been tested in mice and rats (Puspita Dewi et al, 2013) Some people have also used tapak dara as a muscle pain reliever, nosebleed medicine, and swelling relief due to wasp stings (Koul et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, empirically tapak dara is also known to have properties as analgesic (anti-pain) and anti-inflammatory (anti-inflammatory). This is also based on the many studies on the utilization of tapak dara leaf extract as anti-inflammatory(Putri et al, 2019) wound healing and antipyretic drugs whose effectiveness has been tested in mice and rats(Puspita Dewi et al, 2013) Some people have also used tapak dara as a muscle pain reliever, nosebleed medicine, and swelling relief due to wasp stings(Koul et al, 2013).The roots of the tapak dara plant are often used by the community as a treatment by drinking the boiled water, but it is not yet known exactly how much flavonoid content is contained in the roots of the tapak dara plant (Catharanthus roseus). Therefore, the decoction of the roots of the tapak dara plant is used as a medicine, it is necessary to determine the right dose for its use(Kabesh et al, 2015).Therefore, it is necessary to conduct a study that aims to determine the flavonoid content of decoction on the roots of tapak dara (Catharanthus roseus).…”
mentioning
confidence: 99%